Corybas purpureus a New Species of Orchid from United Khasi and Jaintia Hills, Assam - Joseph, J.; Yoganarasimhan, S. N. (Indian Forester, 1967)
Corybas purpureus Joseph et Yog., a new species of orchid from United Khasi and Jaiotia Hills, Assam is described.